2016
DOI: 10.14295/ras.v30i3.28634
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilidade dos Aquíferos Cársticos Sapucari e Maruim, bacia sedimentar de Sergipe-Alagoas

Abstract: Os aquíferos cársticos Sapucari e Maruim são importantes reservas hídricas, responsáveis pelo abastecimento dos municípios de sua abrangência e da grande Aracaju/SE. Os aquíferos cársticos possuem interesse notável, uma vez que as rochas carbonáticas ocupam extensas áreas, com características hidrológicas distintas de grande importância por suas reservas, vazões e qualidade da água. O trabalho teve como objetivo gerar o mapa de vulnerabilidade à contaminação dos aquíferos cársticos com aplicação do método EPIK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…The high and very high classes are related to point infiltration catchments, especially in limestone outcrop areas, indicating the most vulnerable areas in comparison with those with diffuse infiltration. Ribeiro et al (2016) applied the EPIK methodology to the Sapucari and Maruim karstic aquifers, which are important underground water reserves that supply the municipalities with the same names and the large city of Aracaju in Sergipe. Lenhare & Sallun Filho (2019) applied EPIK in the south of São Paulo state, in the Guapiara plateau region, where the authors identified vulnerability with a low association with the high population, and in the Serra of Paranapiacaba where vulnerability was high but associated with low population.…”
Section: First Steps To Understand Intrinsic Vulnerability To Contami...mentioning
confidence: 99%
“…The high and very high classes are related to point infiltration catchments, especially in limestone outcrop areas, indicating the most vulnerable areas in comparison with those with diffuse infiltration. Ribeiro et al (2016) applied the EPIK methodology to the Sapucari and Maruim karstic aquifers, which are important underground water reserves that supply the municipalities with the same names and the large city of Aracaju in Sergipe. Lenhare & Sallun Filho (2019) applied EPIK in the south of São Paulo state, in the Guapiara plateau region, where the authors identified vulnerability with a low association with the high population, and in the Serra of Paranapiacaba where vulnerability was high but associated with low population.…”
Section: First Steps To Understand Intrinsic Vulnerability To Contami...mentioning
confidence: 99%
“…Assim, propõe-se o termo Paisagem dos Aquíferos como forma de delimitar esta região geográfica. Ainda sobre a análise geológica Ribeiro (2001) afirmou que a região é constituída por formações detríticas e carbonatadas, de um modo geral, muito produtivas, caracterizada pela sua grande homogeneidade litológica de características cársicas ou parcialmente cársicas.…”
Section: áRea Em Estudounclassified
“…Thus, karst areas are of great economic and hydrogeological interest because of their signi cant groundwater reserves and mineral occurrence, which is used both in construction and agriculture as well as in tourism (Soedwiwahjono and Pamardhi-utomo 2020). They have a naturally high degree of vulnerability, and depending on the activities performed on this environment, groundwater is increasingly prone to pollution, given the supply of populations, irrigation, and industry (Ribeiro et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, studies focused on the karst aquifers vulnerability theme are of fundamental importance, as they help in activities that aim to protect the recharge areas and, consequently, preserve the good quality of the waters, in face of the technical and nancial limitations resulting from the possible contaminations remediation. Furthermore, they allow the understanding of the different degrees of vulnerability of aquifers, being used as a management tool for local and regional development (Santos et al, 2010;Ribeiro et al 2016).…”
Section: Introductionmentioning
confidence: 99%